Ethnobotanical uses of plants among Rajbansi and Dhimal ethnic communities of eastern Nepal - Siwakoti, Mohan; Shivakoti, Kul Prasad; Karki, Birendra; Siwakoti, Seeta (Journal of Natural History Museum, 2008)
A total of 117 species of angiospermic plants with ethnobotanical values, used by Rajbansi and Dhimal ethnic groups of Jhapa and Morang Districts in eastern terai of Nepal have been described in the paper. J. Nat. Hist. Mus. Vol.22, 2005 p.41-56